2014
DOI: 10.1007/s12298-014-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genetic diversity analysis of soybean (Glycine max (L.) Merr.) germplasm accessions in India

Abstract: Molecular characterization and genetic diversity among 82 soybean accessions was carried out by using 44 simple sequence repeat (SSR) markers. Of the 44 SSR markers used, 40 markers were found polymorphic among 82 soybean accessions. These 40 polymorphic markers produced a total of 119 alleles, of which five were unique alleles and four alleles were rare. The allele number for each SSR locus varied between two to four with an average of 2.97 alleles per marker. Polymorphic information content values of SSRs ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 18 publications
9
21
3
2
Order By: Relevance
“…Bisen et al (2015) detected 2.22 alleles per locus with an average PIC value of 0.199 using 16 SSR markers on 38 soybean varieties in active seed multiplication chain together with all varieties developed and released by JNKVV in India. The average polymorphic information content (PIC) (a measure of the allelic diversity of SSRs) observed in this study was 0.573 which was consistent with previous studies (Widaningsih et al, 2014;Kumawat et al, 2015;Ghosh et al, 2014;Wang et al, 2010). A total of 20 markers excluding BE806308 had the PIC values greater than 0.4 indicating that these markers were highly informative for discriminating and distinguishing released varieties and elite genotypes, and these markers with high PIC values occurred on 14 separate linkage groups indicating that molecular polymorphism was spread across different regions of the genome (Song et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Bisen et al (2015) detected 2.22 alleles per locus with an average PIC value of 0.199 using 16 SSR markers on 38 soybean varieties in active seed multiplication chain together with all varieties developed and released by JNKVV in India. The average polymorphic information content (PIC) (a measure of the allelic diversity of SSRs) observed in this study was 0.573 which was consistent with previous studies (Widaningsih et al, 2014;Kumawat et al, 2015;Ghosh et al, 2014;Wang et al, 2010). A total of 20 markers excluding BE806308 had the PIC values greater than 0.4 indicating that these markers were highly informative for discriminating and distinguishing released varieties and elite genotypes, and these markers with high PIC values occurred on 14 separate linkage groups indicating that molecular polymorphism was spread across different regions of the genome (Song et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Allelic richness (average number of alleles per locus) is an effective index for diversity evaluation but it is largely dependent on the sample size (Hipparagi et al, 2017), suggesting that to improve the allelic richness more genotypes need to be introduced into the breeding program to be able to enhance genetic diversity (Widaningsih et al, 2014). The number of alleles observed in this study is comparable to those reported by Kumawat et al (2015) on 82 indigenous and exotic soybean accessions of different maturity groups and source in India where 2.9 alleles were detected per locus with an average polymorphic information content (PIC) value of 0.58. Similarly, Hipparagi et al (2017) also reported 2.61 alleles with an average PIC value of 0.36 among 75 soybean genotypes assayed by 21 SSR markers in India.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations